Obstetric violence in the stage of pregnancy, labor and puerperium, in the regional hospital Dr. Verdi Cevallos Balda, period 2019 - 2020 - Basurto Mendoza, Gema Priscila (2020)
An important factor during the pregnancy stage is having an adequate emotional state that allows the evolution without obstruction reflected by some type of violence, therefore, this research proposes to characterize obstetric violence in the pregnancy, delivery and postpartum stage in the regional hospital. Dr. Verdi Cevallos Balda period 2019-2020. For this, a non-experimental type of study was used, with a qualitative and quantitative approach; supported by the statistical, bibliographic, analytical and descriptive methods, techniques such as the interview and the survey were used, with the instruments: the interview guide and questionnaire, in a population and sample of 210 women attended in the gynecology area of ​​the hospital . As results, it was obtained that, with 74% women in the postpartum process, they have felt depressed, while with 5% they have felt intimidated by a hospital professional. To conclude, this work shows that there is violence during the stage of pregnancy, childbirth and the puerperium, although this is not attributed to physical factors, but does involve psychological characteristics, reflected in the hospital by health personnel who are immersed in the care provided to users.